Perlindungan Hukum terhadap Investor Perseroan Terbatas Akibat Pandemi Covid-19 - Rezeki, Abdus Salam; Prabowo, Agung Wira Hadi; Samosir, Andi Kesuma Septian; Hsb, Fiqria Muzdalifah; Anggraini, Fitri; Hasril, Syafira; Handani, Syafrillah; Devi, Sri Kumala; Siregar, Emiel Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Coronavirus Disease 2019 (Covid-19) pandemic has prompted countries, including Indonesia, to implement 'abnormal' policies to break the chain of transmission. One approach is the normative juridical method, which involves analyzing and studying relevant laws and regulations to address issues. Legal protection is essential for improving law enforcement and ensuring stability, including in economic and legal matters. Good corporate governance principles are upheld within the Limited Liability Company. Presidential Regulation No. 44 of 2016 lists Closed and Open Business Sectors with Investment Requirements.